Business Identification Number (NIB) Registration Assistance through PAR Approach for MSME Development - Inas Sofia Latif; Mahdi Mahdi; Awaliyyatul ‘Inayah; Novi Humaeroh; Manton Chandra Freddy; Putri Nadia; Aullya Miranda; M. Yasir Fath’hul Adzim; Rasya Abi Bayhaqi; Jasinta Ananda Vinka; Rizal Fahmi (Riau Journal of Empowerment, 2023)
As a form of granting licenses for the implementation of business activities, the legality issued by the authorities to business actors has an important role. The majority of business actors who do not have business legality are caused by limited knowledge and understanding of the level of importance of legality. This also happens to business actors and/or MSMEs in RW 005 Selapajang Jaya Village, Neglasari District, Tangerang City. This service aims to answer problems related to problems that arise, especially to be able to provide understanding in terms of the importance of having business legality and provide assistance regarding business legality. This method of service is carried out with Participatory Action Research (PAR). The implementation of this activity was carried out by the 2023 Syekh-Yusuf Islamic University Tangerang Community Work Lecture team (KKK Ramadhan UNIS 2023) consisting of 10 people. The result obtained from this activity is an increase in understanding from business actors in RW 005 Selapajang Jaya Village, Tangerang City in terms of the importance of having business legality. Assistance in terms of Business Identification Number (NIB) management for business actors who do not have an NIB has also been carried out.